Justification of endolifting in laparoscopic surgery on the kidney (experimental research) - V. M. Grygorenko; S. V. Baydo; S. I. Pryndiuk; Y. R. Deneka (Journal of Education, Health and Sport, 2016)
Grygorenko V. M., BaydoS. V., Pryndiuk S. I., Deneka Y. R. Justification of endolifting in laparoscopic surgery on the kidney (experimental research). Journal of Education, Health and Sport. 2016;6(9):531-538. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.154739